Creating Healthier Academic Work Environments: Exploring Best Practices at Departmental Level - Otrude N. Moyo Dr.; Mary Jo Finney Dr. (Academic Chairpersons Conference Proceedings, 2016)
Workplace health is crucial for student, faculty and staff success. Using experiential wisdom we highlight challenges linked to the rise of ‘neoliberal university’ characterized by a shift from education as a public good to values of entrepreneurialism, profit making and its impact on the well-being of academic faculty and staff.
Keywords: workplace well-being; faculty well-being; work place health; academic work environment; psychological healthy